Indirect Spectrophotometric Method for Determination of Niclosamide via Oxidation Reaction and Bleaching colour of Methylene Blue Dye - Sahar A. Fathi; Nabeel S.Othman; Amer Th. AL-Taee (African Journal of Advanced Pure and Applied Sciences, 2023)
Simple, delicate and sensitive method for estimation niclosamide (NICA) as pure, pharmaceutical and veterinary formulations. The method is based on the oxidation of niclosamide (NICA) by using an excess of the oxidizing agent N-bromosuccinimide (NBS) in an acidic medium. Then the unreacted N-bromosuccinimide is reacted with methylene blue (MB) dye where the color of the dye is bleached and measured at the maximum wavelength of the dye 664 nm. The linear graph of absorbance versus concentration indicates that Beer’s law applies within the concentration range 2-6 µg.mL-1 of niclosamide. The determination coefficient (R2) was found to be 0.9955 and molar absorptivity value was 4.6546x104 L.mol-1 .cm-1and the Sandell’s sensitivity value was 0.00702 μg .cm-2 and the quantitative limit attained (LOQ) was 0.0148 µg.mL-1. The limit of detection (LOD) was 0.0044 µg.mL-1. with -0.15% to -0.90% relative error and relative standard deviation was 0.65 to 1.93